Seleção de conteúdos no curso de iniciação musical para crianças do programa Guri - Bergantin, Eglem das Neves (Universidade Federal de São Carlos, 2025)
This study was based on the question “What, why and for what purpose do teachers of the Guri’s Musical Initiation for Children (GMIC) course teach what they teach?” Based on this question, the general objective of this research was to investigate, from the teachers’ perspective, the content selection process in the GMIC course. As specific goals, we aim to: identify which contents are worked on by teachers; investigate why they select these contents and why they consider them valid musical knowledge for GMIC; and verify, in their opinion, what is the purpose of the music teaching they carry out. As reference authors, we based ourselves on Gimeno Sacristán (2013) in the area of curriculum, Zabala (1988) on the typology of content, Contreras (2002) and his conception of professional autonomy of the teacher, Libâneo (2013) and the criteria for content selection, Chervel (1990) and Goodson (1995) in the field of the history of subjects, Fonterrada (2008) on the history of music education in Brazil, and Keith Swanwick (1979) and his C(L)A(S)P model. As a data collection method, we used the semi-structured interview, a method in which six teachers of the GMIC course, from different locations in the State of São Paulo, were interviewed. The analyses demonstrated that there is a strong influence of the conservatory model in the GMIC course. However, the characteristics of the conservatory model coexist with the approaches of active methods in music education, pointing to a transition phase in the conception of music teaching for children. We found in the data that the basic musical parameters are hegemonic content and inherited in music teaching for children; also, we notice the imbalance between musical activities in the curriculum (mainly, the low presence of composition), the loss of teacher’s autonomy due to structural issues of Guri, and the fragility of the professional area of music teaching.
Content selection in the musical initiation course for children of the Guri program
Keywords: Educação musical; Currículo; Seleção de conteúdos; Music education; Curriculum; Content selection; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA